PARTISIPASI SUAMI DALAM PELAKSANAAN KELAS IBU HAMIL - Fadmiyanor, Isye; Aryani, Yeni; Vitriani, Okta (EBIMA : Jurnal Edukasi Bidan di Masyarakat, 2022)
Education during pregnancy is important to prepare couples to become parents. In carrying out their role, pregnant women and their partners need good information about the health of both the mother and the fetus. In Indonesia, the program organized by the government to support the increase of knowledge and behavior change of mothers and husbands is a class program for pregnant women. In the implementation of this class, pregnant women are often only attended by pregnant women, even though the husband's activity in attending classes for pregnant women in accompanying mothers greatly influences the physical and psychological changes of pregnant women and supports the implementation of classes for pregnant women. This community service activity is carried out by providing online counseling via zoom meetings and offline which are carried out door to door, which is attended by 10 pairs of pregnant women. The results of community service were obtained that 60% of husbands could not take classes for pregnant women due to work factors, there was an increase in knowledge in husbands, namely from 77 to 95, pregnant women from 75 to 9. Therefore, to increase partner participation in the implementation of pregnant women classes it is necessary to conduct socialization to couples regarding classes for pregnant women and cooperation with local community leaders as well as re-run the pregnant women class program which was not implemented during the Covid-19 pandemic. Keyword: Husband's Participation, Maternity Class